Lysosomal signature in Diffuse Large B Cell Lymphoma - marker expression correlation with disease prognosis - Shastry, Prakhya (My University, 2025)
Introduction: Diffuse Large B Cell Lymphoma (DLBCL) is a group of highly heterogenous and aggressive malignancies, with an immediate need for improved diagnostics to differentiate the various disease subtypes, as 40-60 % of the patients relapse after initial treatment due to disease heterogeneity. Lysosomal compartments are important in mediating cell signalling events in B cells, and, lysosomal proteins have also been detected in released extracellular vesicles (EVs). Aim and Hypothesis: This study aims to evaluate the expression level of the ubiquitous Lysosomal Associated Membrane Protein-1 (LAMP-1) and intralysosomal enzyme Cathepsin S in DLBCL cell lines, EVs and in tissues of patients with DLBCL, and evaluate their expression in comparison to healthy donor samples. Methodology: The expression of LAMP-1 and Cathepsin S were evaluated using confocal microscopy for cell lines whereas the tissue microarray slices containing DLBCL and healthy donor tissues were stained with immunohistochemistry. The EVs isolated by size exclusion chromatography were visualized under a transmission electron microscope and further analysed by enzyme linked immunosorbent assay (ELISA) and Western blot. Results and Conclusion: The data from this study supports our hypothesis that the lysosome compartment is deregulated and the expression level of distinct lysosomal proteins is significantly elevated in the DLBCL tissue samples when compared to the healthy samples. The expression and localization of lysosomal structures within the cells appeared to be differently organized and putatively in a subtype-specific way. The marker analysis in patient tissues confirm the differently organized lysosome populations: to fully understand the varying signature in the different subtypes requires a larger sample panel.
Keywords: Diffuse large B cell lymphoma, Lysosomal markers, Biomarkers, Extracellular vesicles